Dignity, Wisdom, and Tomorrow's Ethical Business Leader. (8th September 2016) - Hicks, Donna; Waddock, Sandra
Abstract: This article examines the role wisdom and dignity play in developing ethical business leaders, or what we call shamanic leaders, for the twenty‐first century. We define wisdom as the integration of moral imagination (the good), systems understanding (the true), and aesthetic sensibility (the beautiful) into decisions, actions, and practices in the service of a better world. Dignity is our inherent value, worth, and vulnerability, a core aspect of humanity that each of us is born with. The challenges of developing shamanic leaders, i.e., individuals who evidence the shamanic attributes of healing, connecting, and sensemaking, are discussed, including how to think about and embody wisdom, and the learning that is required to understand and lead with dignity. We argue that dignity and wisdom can be learned and provide the reader with insights into what is required to promote an inclusive and integrated culture where human flourishing and well‐being are at the core of ethical leadership.